Upaya Pembentukan Karakter Bangsa Berjiwa Nasionalis Dengan Tayangan Film “Battle Of Surabaya” - Tomy Rizky Izzalqurny; Ajeng Purbaningrum; Sayyid Achmad Abdillah; Tioryta Grasella Sijabat (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2023)
The character of nationalism is very important to be instilled as an effort to build a strong character in order to fortify the golden milestone of the Indonesian nation (the younger generation) against the negative impacts of globalization. The activity of “Watching with Film Nationalism” was carried out to foster the nationalist and patriotic spirit of the younger generation as a golden milestone for the Indonesian nation. The method used is planning through observation and adjustment of work programs, submission of proposals, pre-implementation, implementation of activities, and evaluation of activities. This activity was carried out in December at one of the elementary schools in the village of MI Miftahul Huda Duwet Krajan with the target activities of students in grades IVb, V, and VI. This activity achieved results in the form of increasing the knowledge of MI Miftahul Huda students to be able to know more about the heroes who contributed to Indonesia, to form a patriotic character, and proud to be part of the Indonesian nation.Keywords: nationalism; patriotism; students Abstrak: Karakter nasionalisme sangatlah penting untuk ditanamkan sebagai upaya pembentukan karakter yang kuat dalam rangka membentengi tonggak emas bangsa Indonesia (generasi muda) akan dampak negatif dari globalisasi. Kegiatan “Nonton Bareng Film Nasionalisme” dilaksanakan untuk menumbuhkan semangat nasionalis dan patriotis generasi muda sebagai tonggak emas bangsa Indonesia. Metode yang digunakan adalah perencanaan melalui observasi dan penyesuaian program kerja, pengajuan proposal, prapelaksanaan, pelaksanaan kegiatan, dan evaluasi kegiatan. Kegiatan ini dilaksanakan pada bulan desember di salah satu sekolah dasar desa duwet krajan MI Miftahul Huda dengan sasaran kegiatan siswa kelas IVb, V dan VI. Kegiatan ini mencapai hasil berupa  peningkatan pengetahuan siswa MI Miftahul Huda untuk dapat lebih mengenal tokoh pahlawan yang berjasa di Indonesia, untuk membentuk karakter patriotis dan bangga menjadi bagian dari Bangsa Indonesia.Kata kunci: nasionalisme; patriotisme; siswa